1986
DOI: 10.1111/j.1365-2222.1986.tb01960.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leukotriene D4 on nasal mucosal blood flow, nasal airway resistance and nasal secretion in humans

Abstract: Summary The possible role of leukotriene D4(LTD4)in nasal allergy was investigated in healthy volunteers. Nasal blood flow, nasal airway resistance, nasal discharge and nasal itching and sneezing were examined. LTD4 was found to induce a dose‐response related increase in nasal mucosal blood flow as measured by laser‐Doppler flowmetry. Histamine exhibited similar effects on blood flow in the same concentration range. Nasal airway resistance as recorded by rhinomanometry, increased in a dose‐related manner after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
103
1
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(109 citation statements)
references
References 20 publications
3
103
1
2
Order By: Relevance
“…Particularly leukotrienes such as LTB 4 and leukotriene C 4 , which rise in the nasal fluid of rhinitis patients, are generated and released by virus-infected cells of the respiratory tract (Ananaba and Anderson, 1991;van Schaik et al, 1999;Gentile and Skoner, 2001;Gentile et al, 2003). Leukotrienes such as LTD 4 applied directly to the nasal mucosa of noninfected individuals reproduced symptoms of nasal congestion and rhinorrhea (Bisgaard et al, 1986). Treatments with 5-LO enzyme inhibitors or cysteinyl leukotriene receptor antagonists have been shown to induce a significant clinical benefit because these compounds reduces nasal congestion in allergic rhinitis (Naclerio et al, 1991;Liu et al, 1998;Meltzer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly leukotrienes such as LTB 4 and leukotriene C 4 , which rise in the nasal fluid of rhinitis patients, are generated and released by virus-infected cells of the respiratory tract (Ananaba and Anderson, 1991;van Schaik et al, 1999;Gentile and Skoner, 2001;Gentile et al, 2003). Leukotrienes such as LTD 4 applied directly to the nasal mucosa of noninfected individuals reproduced symptoms of nasal congestion and rhinorrhea (Bisgaard et al, 1986). Treatments with 5-LO enzyme inhibitors or cysteinyl leukotriene receptor antagonists have been shown to induce a significant clinical benefit because these compounds reduces nasal congestion in allergic rhinitis (Naclerio et al, 1991;Liu et al, 1998;Meltzer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nasal insufflation studies show that both leukotriene C4 (LTC4) and leukotriene D4 (LTD4) induce an increase in nasal mucosal blood flow and nasal airway resistance. [19][20][21] Montelukast is an orally active, highly selective cysteinyl leukotriene type-1 receptor antagonist of leukotreine D4, with affinities approximately two-fold greater than the natural ligand. It is rapidly absorbed, achieving peak plasma concentration (Cmax) in three to four hours and with a mean bioavailability of 64% following a 10 mg oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…16 Their activities include smooth-muscle contraction, small vessel dilatation, increase in blood vessel permeability, promotion of glycoprotein secretion from epithelial glands, and increase of nasal blood flow and airway resistance. [32][33][34][35][36] It has been demonstrated that leukotrienes are also produced in the conjunctiva 37 and are detectable in tear fluids of patients affected by allergic conjunctivitis including VKC. [38][39][40] Indeed LT concentration in tears increases in allergic subjects following allergen challenge.…”
Section: Vernal Keratoconjunctivitis S Bonini Et Al 346mentioning
confidence: 99%